2013
DOI: 10.1007/s00018-013-1375-4
|View full text |Cite
|
Sign up to set email alerts
|

The tumor suppressor annexin A10 is a novel component of nuclear paraspeckles

Abstract: Annexin A10 is the latest identified member of the annexin family of Ca(2+)- and phospholipid-binding proteins. In previous studies, downregulation of annexin A10 was correlated with dedifferentiation, invasion, and tumor progression, pointing to a possible tumor suppressor role. However, the biochemical characteristics and functions of annexin A10 remain unknown. We show that annexin A10 displays biochemical characteristics atypical for an annexin, indicating a Ca(2+)- and membrane-binding-independent functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 59 publications
0
25
0
Order By: Relevance
“…They also play critical roles in the inhibition of coagulation and inflammation, reviewed in [32, 33]. ANXA10, is a member of the ANNEXIN gene family; however, it has only one Ca 2+ binding site [34] and displays a low capacity for phospholipids that are dependent on Ca 2+ [35]. The functions of ANXA10 in vivo, including those relevant to embryonic mortality, have not yet been evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…They also play critical roles in the inhibition of coagulation and inflammation, reviewed in [32, 33]. ANXA10, is a member of the ANNEXIN gene family; however, it has only one Ca 2+ binding site [34] and displays a low capacity for phospholipids that are dependent on Ca 2+ [35]. The functions of ANXA10 in vivo, including those relevant to embryonic mortality, have not yet been evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…We found that the annexin‐A10 (ANXA10) gene was more strongly expressed in cells receiving statins than those not receiving statins. ANXA10 is the most recently identified member of the annexin family of calcium‐ and phospholipid‐binding proteins . In previous studies, down‐regulation of ANXA10 was correlated with dedifferentiation, invasion, and tumor progression, pointing to a possible tumor suppressor role .…”
Section: Introductionmentioning
confidence: 96%
“…ANXA10 is the most recently identified member of the annexin family of calcium‐ and phospholipid‐binding proteins . In previous studies, down‐regulation of ANXA10 was correlated with dedifferentiation, invasion, and tumor progression, pointing to a possible tumor suppressor role . However, whether ANXA10 has a specific function in prostate cancer remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Paraspeckle component 1 (PSPC1), one of the three DBHS proteins, also colocalized with anxA10GFP in resting cells. This study indicated that colocalization and interaction between SFPQ and annexin 10A have an influence on the apoptosis (Quiskamp et al, 2014). Annexin 10A binding to SFPQ in the nucleus, and the overexpression of annexin 10A is reported an inducing factor for tumor cell apoptosis.…”
Section: Sfpqmentioning
confidence: 68%